Literacy brokering among the international students of a public university - Humaira, Raslie; Yuen, Chee Keong (Universiti Kebangsaan Malaysia, 2017)
The influx of international students to Malaysia in pursuance of tertiary education has created the urgency to ascertain the English literacy struggles faced by these students in the Malaysian classrooms as well as the suitability of the current pedagogical practices in addressing their existing literacy practices. Insights on the aforementioned aspects could be gained by examining the students’ literacy brokering engagements. Literacy brokering refers to an act of seeking informal help in various forms from fellow language users when facing unfamiliar texts or text-oriented practices and events. This case study therefore examined the literacy brokering phenomenon occurring within a Malaysian university’s intensive English Language class. The research participants consisted of 15 international students from five different countries. The specific objectives of the study were to: (i) identify the themes involved in literacy brokering interactions occurring in the Malaysian university English language classroom context; and (ii) describe the literacy practices of the international students in their English class. Through the methods of audio and video recording, 98433 words of transcribed data were collected. An in-depth analysis of the data revealed the primary brokering theme to be the English language system, specifically aspects of grammar and semantics. However culture and genre-based themes were also apparent. The brokerage of culture and genre stemmed from the mismatch between the participants’ existing literacy knowledge with those in their current context of living. The findings create an andragogic importance to include learners’ socio-cultural schemata in designing and carrying out non-native language pedagogy. In the spirit of contextualising learning experience, future works could focus on analysing the literacy brokering occurrences in other non-native English Language classrooms such as Singapore and Hong Kong.